Safety and quality protection of cochlear implantation during the COVID-19 pandemic - Singh, Jyoti; Jha, Shruti; Kumar, Alekh; Singh, Rakesh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: With the emergence of the COVID-19 pandemic, there has been an urgent need to formulate guidelines for safety during aerosol-generating surgeries like cochlear implantation. Although elective, these procedures are crucial to prelingually deaf children so they can develop speech and language skills. Our study is based on guidelines we formulated for cochlear implantation during the COVID-19 pandemic, emphasizing the need for utilizing reverse transcription-polymerase chain reaction (RT-PCR), isolation, and proper protective equipment that is safe yet practical. Methods: This study was carried out between February 2020 and December 2021. Forty-nine cochlear implantations were carried out at our center following our guidelines during three safe windows when the R factor was <1. All patients underwent serial RT-PCR testing, proper isolation, and were operated on by surgeons who used effective and practical protective equipment. Results: None of the 49 patients who underwent cochlear implant surgery or the health care workers involved in their care developed clinical features or tested positive for COVID-19 postoperatively. There were also no cases of readmission for COVID-19 after the patients’ discharge from the hospital. Conclusions: Cochlear implantation is an essential procedure that can be safely carried out during a pandemic if guidelines are followed ardently and personal protective equipment is used effectively.